Research on the Development Status and Optimization Strategies of Poetry Immersion Experience - Chen, Ruiying; Li, Hanchi; Xu, Ruiqing; Li, Hantong; Wang, Xiaohua (International Journal of Global Economics and Management, 2024)
In the strategic layout of "creative transformation and innovative development of excellent tradi-tional culture" at the cultural level, the Chinese Poetry Conference broadcast on CCTV, and the 2024 Spring Festival Gala Poetry Chang'an, all of which can be seen that Chinese poetry has shown a vigorous development trend, and the intermingling of poetry dissemination and science and tech-nology has become increasingly close, and the "The Longest Day In Chang'an Theme Block" located in Xi'an is even more typical. The "The Longest Day In Chang'an Theme Block" in Xi'an is more typical. This paper researches the development status of a poetry immersion experience and proposes optimization strategies through field research, questionnaire survey, and SPSS analysis, and then combines the theory of five senses marketing and industrial integration.